Використання структур даних для реалізації черги подій в іграх з механікою обмеження часу - Бухало, В. О. (ХНУРЕ, 2024)
The current work investigates the use of data structures in developing program code for managing time and events in a gaming environment, where the execution of a particular action is time-constrained. Creating such a tool involves implementing a basic data structure of a queue and modifying it to track and control each player’s time, manage the sequence of turns, and respond to events and actions of players within a specified time period. Using the data structure of a queue, the developed software module ensures efficient execution of events in the game process. The work utilized the Node.js runtime environment and the TypeScript programming language.
Keywords: структура даних; механіка обмеження часу; game